2018
DOI: 10.1155/2018/4571368
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of Biodegradable Polylactide/Thermoplastic Starch/Nanosilica Composites: Effects of Plasticizer and Nanosilica Functionality

Abstract: The effect of plasticizer (polydimethylsiloxanol) and neat (SiO2) or modified (having amine functional groups) silica (A-SiO2) on morphology, thermal, mechanical, and rheological properties of PLA/TPS blends compatibilized by maleated PLA (MPLA) was investigated. Toughened PLA/MPLA/TPS (60/10/30) blend containing 3 wt.% of plasticizer and various contents (1, 3, or 5 wt.%) of silica were prepared in a corotating twin-screw extruder. From SEM, it is clear that plasticized PLA/MPLA/TPS blend continuous porous st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
10
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 56 publications
(81 reference statements)
5
10
0
Order By: Relevance
“…The depressed T g of PLA after blending with TPS (approximately 10–17°C) reflected the increased free volume of the PLA phase or the enhanced mobility of PLA chains, and this may be due to the migration of glycerol plasticizer from the TPS phase to the PLA phase, as well as the interference of starch molecules. Similar results were reported by Park et al, 41 Sirin et al, 46 and Jeziorska et al 47 The lower T cc of PLA in the PLA/TPS blend films compared with that of the neat PLA indicated that TPS could act as a nucleating agent for PLA 12,41 . In addition, the reduced T m of PLA in the PLA/TPS blend films compared with that of the neat PLA film may be explained by the less perfect crystalline structure of PLA formed in the blend.…”
Section: Resultssupporting
confidence: 90%
“…The depressed T g of PLA after blending with TPS (approximately 10–17°C) reflected the increased free volume of the PLA phase or the enhanced mobility of PLA chains, and this may be due to the migration of glycerol plasticizer from the TPS phase to the PLA phase, as well as the interference of starch molecules. Similar results were reported by Park et al, 41 Sirin et al, 46 and Jeziorska et al 47 The lower T cc of PLA in the PLA/TPS blend films compared with that of the neat PLA indicated that TPS could act as a nucleating agent for PLA 12,41 . In addition, the reduced T m of PLA in the PLA/TPS blend films compared with that of the neat PLA film may be explained by the less perfect crystalline structure of PLA formed in the blend.…”
Section: Resultssupporting
confidence: 90%
“…The decrease in the modulus after application of the SNP in the polymer matrix has also been reported in other studies 18,41 . Furthermore, the storage modulus in the glassy region is higher for the SLPUF1 than the SLPUF0.5 and SLPUF0.1 samples, which is due to the stiffness of solid nanoparticles 45 46 …”
Section: Resultssupporting
confidence: 81%
“…The addition of RH with an irregular shape may interfere with the crystallization process of the PLA, creating difficulty in chain rearrangement and disrupting the intermolecular attraction between the PLA chains themselves. Moreover, the chain mobility of PLA has been increased, owing to the plasticizing effect of GLY plasticizer 44 . This is corresponded with the increased impact strength, as discussed in the previous section.…”
Section: Resultsmentioning
confidence: 53%